EVALUATION OF SUBACUTE SODIUM FLUORIDE TOXICITY ON SPERMATOZOA AND TESTICULAR TISSUE OF MALE WISTAR RATS - D. K. GIRI*, R. C. GHOSH, D. K. KASHYAP; GOVINA DEWANGAN (The Bioscan, 2013)
The adverse influence of fluorides on male reproductive system has become a major concern in many countries. The present study was focussed to determine the effect of daily oral administration of sodium fluoride for 28 days on seminal characteristics of male Wistar rats at three dose levels. Intoxication of sodium fluoride to Wistar rats of group II (5mg/kg body weight, orally), group III (25 mg/kg body weight, orally) and group IV (50 mg/kg body weight, orally) caused dose dependent decrease (p ≤ 0.01) in epididymal sperm motility, progressive sperm motility, sperm concentration and live spermatozoa along with simultaneous increase in dead spermatozoa as compared to the rats of group I (control). There was a dose dependent increase (p ≤ 0.01) in percent morphological abnormalities (head, tail and multiple) of spermatozoa in group III and group IV as compared to rats of control group and group II. Overall, the maximum mean values for various sperm abnormalities were recorded in group IV rats. Hence, sodium fluoride exerts significant cytotoxicity to spermatozoa at higher doses adversely affecting the male reproductive system.